(untitled) (The Journal of Interdisciplinary Human Studies, 2025)
This article examines the significance of al-Bidaya wa’n-Nihaya, authored by the Damascus-based exegete and historian Abu al-Fida Ibn Kathir, as an important source for Islamic history and for documenting the events of the period in which the author lived. It is well known that in the 14th century, under Mamluk rule in Egypt and the Levant, great attention was devoted to historical and biographical works. Historiography flourished, and historians-many of whom were also distinguished scholars of religion–held high-ranking positions in the state. Among such works, al-Bidaya wa’n-Nihaya stands out as one of the most renowned, gaining significance particularly for Ibn Kathir’s consistent and detailed account of the events of his own era.